Arbeitsregulation in der ambulanten Pflege Handlungsfelder kollektiver Interessenvertretung - Becker, Nils (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2014)
Working conditions in out-patient care are considered precarious. While more and more nurses are employed in care at home, no appreciable collective representation of interests seems to be emerging that can respond to the specific regulatory requirements in terms of employees. Opportunities for trade union activities sectors are presented which were previously considered strongly subjectivized through social orientation and employment without boundaries and so less promising fields of collective regulated working conditions.